Бухгалтерський аутсорсинг як інноваційний інструмент досягнення економічних переваг - Давидюк, Тетяна Вікторівна; Легоцька, Ю. І. (Одеський національний політехнічний університет, 2018)
В статті розглянуто сутність "аутсорсинг", проаналізовано напрямки класифікації атусорсингу, визначено місце бухгалтерського аутсорсингу серед інших видів аутсорсингу, встановлено його основні переваги та недоліки, виділено етапи та обґрунтовано критерії вибору аутсорсера на ринку аутсорсингових послуг з точки зору їх якості та ефективності. Запропоновано підприємству-споживачу аутсорсингових послуг орієнтуватись на кількісних метода оцінки, таких як економічний ефект, що полягає в економії витрат при веденні обліку аутсорсером порівняно із веденням обліку штатом бухгалтерів. Обґрунтовано, окрім кількісних, використовувати й якісні методи оцінки ефективності бухгалтерського аутсорсингу, що виражено в запропонованому алгоритмі відбору майбутнього партнера по аутсорсингу.

The paper considers outsourcing of bookkeeping. Definition of outsourcing is stated and directions of classification are analyzed. The place of accounting outsourcing among other types of outsourcing, its main advantages and disadvantages, stages are outlined. The criteria for choosing an outsourcer in appropriate market taking into account the quality and efficiency have been justified. The enterprise-consumer of outsourcing services is offered to be guided by quantitative method of estimation such as calculating of the economic effect, which consists in saving costs when accounting is performed by outsourcer in comparison with keeping records by state of accountants. Algorithm for selecting a future accounting outsourcing partner including qualitative methods for evaluating the service efficiency has been proposed.
Accounting outsourcing as an innovative instrument for achieving economic benefits
Keywords: аутсорсинг; бухгалтерський облік; бухгалтерський аутсорсинг; аутсорсингова компанія; споживач аутсорсингових послуг; outsourcing; accounting; accounting outsourcing; outsourcing company; consumer outsourcing services